An alternative approach to deal with the absence of clinical trials: a proportional meta-analysis of case series studies - El Dib, Regina [UNESP]; Nascimento Junior, Paulo do [UNESP]; Kapoor, Anil (Sociedade Brasileira para o Desenvolvimento da Pesquisa em Cirurgia, 2013)
PURPOSE: Systematic reviews are criticized for frequently offering inconsistent evidences and absence of straightforward recommendations. Their value seems to be depreciated when the conclusions are uncertain. To describe an alternative approach of evaluating case series studies in health care when there is absence of clinical trials. METHODS: We provide illustrations from recent experiences. Proportional meta-analysis was performed on surgical outcomes: (a) case series studies, (b) use of cryoablation or radiofrequency ablation, and (c) patients with small renal cell carcinoma. The statistically significant difference between both interventions studied was defined if their combined 95% confidential interval (CI) did not overlap. RESULTS: As demonstrated by the example, this analysis is an alternative approach to provide some evidence of the intervention´s effects under evaluation and plotting all available case series in the absence of clinical trials for the health field. CONCLUSIONS: Although we are leading to a low level of evidence to determine efficacy, effectiveness and safety of interventions this alternative approach can help surgeons, physicians and health professionals for a provisionally decision in health care along with their clinical expertise and the patient´s wishes and circumstances in the absence of high-quality primary studies. It´s not a replacement for the gold standard randomized clinical trial, but an alternative analysis for clinical research.
Keywords: Review; Methodology; Clinical Trials as Topic; Meta-analysis; Time Series Studies